The Neural Progenitor Cell-Associated Transcription Factor FoxG1 Regulates Cardiac Epicardial Cell Proliferation - Lucy Pilcher; Lara Solomon; Julie A. Dragon; Dhananjay Gupta; Jeffrey L. Spees (Hindawi Limited, 2024)
The epicardium is a layer of mesothelial cells that covers the surface of the heart. During development, epicardial cells undergo epithelial-to-mesenchymal transition (EMT) to form multipotent precursors that migrate into the heart and contribute to the coronary vasculature by differentiating into adventitial fibroblasts, smooth muscle cells, and endothelial cells. Epicardial cells also provide paracrine signals to cardiac myocytes that are required for appropriate heart growth. In adult hearts, a similar process of epicardial cell EMT, migration, and differentiation occurs after myocardial infarction (MI, heart attack). Pathological cardiac hypertrophy is associated with fibrosis, negative remodeling, and reduced cardiac function. In contrast, aerobic exercises such as swimming and running promote physiological (i.e., beneficial) hypertrophy, which is associated with angiogenesis and improved cardiac function. As epicardial cell function(s) during physiological hypertrophy are poorly understood, we analyzed and compared the native epicardial cells isolated directly from the hearts of running-exercised mice and age-matched, nonrunning littermates. To obtain epicardial cells, we enzymatically digested the surfaces of whole hearts and performed magnetic-activated cell sorting (MACS) with antibodies against CD104 (integrin β4). By cDNA microarray assays, we identified genes with increased transcription in epicardial cells after running exercise; these included FoxG1, a transcription factor that controls neural progenitor cell proliferation during brain development and Snord116, a small noncoding RNA that coordinates expression of genes with epigenetic, circadian, and metabolic functions. In cultured epicardial cells, shRNA-mediated FoxG1 knockdown significantly decreased cell proliferation, as well as Snord116 expression. Our results demonstrate that FoxG1 regulates epicardial proliferation, and suggest it may affect cardiac remodeling.